Strategy for reduction and fixation of complex mandibular fractures. A case report (Research, Society and Development, 2021)
Mandibular fractures are relatively common, but fracture patterns and treatment modalities vary depending on the anatomical and biomechanical characteristics of the region. This article aims to carry out a case report of an 80-year-old patient, victim of a fall from his own height, with an atypical mandibular fracture in the left mandibular body and angle region, with three fracture lines uniting in the posterior region of mandibular branch. Treatment was instituted according to the observed fracture pattern and following the principles of rigid internal fixation, with good postoperative evolution, even if the patient is still being followed up. Thus, it can be concluded that the proper management of any fracture pattern and an adequate follow-up of each case is necessary to reduce the incidence of postoperative complications.